(untitled) (The International Journal for Scientific Research, 2025)
The virtual world, represented by social media networks, is a place for exchanging information, events, and opinions, and for engaging in conversations for many people. This has increased the public’s use of these networks. With increased use, public concerns regarding user identity have increased. Therefore, this study aimed to investigate the extent to which digital security has influenced the transition from using unreal names to real names on X networking site by examining the reasons for concealing identity and then the reasons for switching from unreal names to real names among female university students using the X Network (formerly Twitter). This study utilized a qualitative methodology based on in-depth interviews with 25 female students from King Abdulaziz University. The study revealed that 68% of the study sample used an unreal name when they first joined the X Network, while 64% of the study sample switched from using unreal names to real names.